Membrane shape-mediated wave propagation of cortical protein dynamics - Zhanghan Wu (Nature Portfolio, 2018)
Traveling waves in the cell cortex can propagate much faster than actin waves, and the mechanism is unknown. Here the authors propose a mechanochemical feedback model for traveling waves that incorporates membrane shape changes and recruitment of F-BAR proteins that enables fast wave propagation.